The twisted ones : the graphic novel - Cawthon, Scott, 1971-; Breed-Wrisley, Kira; Hastings, Christopher, 1983- (Cawthon, Scott, 1971- Five nights at Freddy's., 2021)
A year after the tragedy at Freddy Fazbear's Pizza, eighteen-year-old Charlie is trying to move on when the nightmares start. Then a series of mutilated bodies begin appearing around her school. Soon Charlie is drawn back into her father's world with its twisted creations--one of which is hunting Charlie.